South Africa’s protracted struggle for equal distribution and equitable access – still not there - van Rensburg, Hendrik CJ (BioMed Central, 2014)
The purpose of this contribution is to analyse and explain the South African HRH case, its historical evolution, and post-apartheid reform initiatives aimed at addressing deficiencies and shortfalls. HRH in South Africa not only mirrors the nature and diversity of challenges globally, but also the strategies pursued by countries to address these challenges. Although South Africa has strongly developed health professions, large numbers of professional and mid-level workers, and also well-established training institutions, it is experiencing serious workforce shortages and access constraints. This results from the unequal distribution of health workers between the well-resourced private sector over the poorly-resourced public sector, as well as from distributional disparities between urban and rural areas. During colonial and apartheid times, disparities were aggravated by policies of racial segregation and exclusion, remnants of which are today still visible in health-professional backlogs, unequal provincial HRH distribution, and differential access to health services for specific race and class groups. Since 1994, South Africa’s transition to democracy deeply transformed the health system, health professions and HRH establishments. The introduction of free-health policies, the district health system and the prioritisation of PHC ensured more equal distribution of the workforce, as well as greater access to services for deprived groups. However, the HIV/AIDS epidemic brought about huge demands for care and massive patient loads in the public-sector. The emigration of health professionals to developed countries and to the private sector also undermines the strength and effectiveness of the public health sector. For the poor, access to care thus remains constrained and in perpetual shortfall. The post-1994 government has introduced several HRH-specific strategies to recruit, distribute, motivate and retain health professionals to strengthen the public sector and to expand access and coverage. Of great significance among these is the NHI Plan that aims to bridge the structural divide and to redistribute material and human resources more equally. Its success largely hinges on HRH and the balanced deployment of the national workforce. Low- and middle-income countries have much to learn from South African HRH experiences. In turn, South Africa has much to learn from other countries, as this case study shows.